EFFECT OF BIOFERTILIZERS ON GROWTH AND YIELD OF POTATO IN NORTH EASTERN HILLS OF INDIA - Baishya, L. K.; Gupta, V. K.; Lal, S. S; Das, B. K.; Kumar, Manoj (Potato Journal, 2013)
In a field experiment conducted during summer season of 2002 and 2003 at Shillong, two levels of N and P(75 and 100 percent) were evaluated in combination with biofertilizers, viz., Azotobacter, Bacillus and both Azotobacter + phosphobacterium. The highest tuber yield was recorded in treatment consisting of 100% NP + phosphobacterium + Azotobacter + 1% urea +1% sodium bicarbonate solution (233.8 q/ha) followed by application of 75% NP + Azotobacter + phosphobacterium + 1% urea + 1% sodium bicarbonate solution (229.8 q/ha). Treatment of seed tubers with Bacillus also gave at par tuber yield. The results revealed that input of inorganic fertilizers, viz., N and P can be reduced by 25% when biofertilizers are used for potato production.